HISTOPATHOLOGY of MIXED INFECTIONS in REDCLAW CRAYFISH (Cherax quadricarinatus) TISSUES - Syahidah, Dewi; Owens, Leigh (JFMR (Journal of Fisheries and Marine Research), 2020)
Redclaw crayfish (C. quadricarinatus) diseases have become an important issue with a number of reports from farms in Australia since the 1990s. About 30 Adult crayfish were housed at SVBS JCU and were given mixed food as required for 3wks. Crayfish samples were preserved at D21 by injecting the cephalothorax and abdominal muscles with Davidson’s fixative (10mL of Davidson per 1g crayfish). Histological examination was conducted by longitudinally slicing the cephalothorax, abdomen, and gill tissues at approximately 2-3mm thickness to obtain separate histological sections of the tissues. Sections were cut at 5µm and stained with Mayer’s hematoxylin and eosin (H&E), Gram-Twort, Periodic Acid-Schiff (PAS), and phosphotungstic acid-eosin. An Olympus EC microscope was used to view the sections and the photographs were taken using QCapture.Pro. The results showed melanisation in the hepatopancreatic tissues, hemolymph and gills; Haemocytic aggregation in the hemolymph; Fungal hyphae in the gills; Multiple nodule formation surrounded by melanisation with continued haemocytic aggregation and whirling, early stage of catabolism and bacterial colonies were identified in the muscles. In conclusion, histopathological analyses in this study that redclaw crayfish is susceptible for mixed infection from bacteria, fungi, and virus.